Level Of Knowledge General Practitioner About Determination Of Natural Death And Unexpected Unnatural Death At Rsd Gunung Jati Kota Cirebon 2022 - Andri Andrian Rusman; Syafiq Indra Sugiri; Dewi Ratih Handayani; Andri Nur Rochman (Jurnal EduHealth, 2023)
Cases of death have two sides, namely natural cases due to the occurrence of illness and cases unexpected to be unnatural due to the involvement of elements of violence/crime. General practitioners have competence in medicolegal procedures in death cases, namely determining natural and unexpected unnatural deaths so that they can provide an explanation to the patient's family for further procedures. The purpose of this study was to describe the level of knowledge of general practitioners regarding medico-legal procedures in determining natural and unexpected unnatural cases of death at RSD Gunung Jati Kota Cirebon. The research design that has been done is descriptive cross sectional by using a questionnaire guide and free interviews. The results of this study can be concluded that the general practitioner's level of knowledge regarding the determination natural death and unexpected unnatural cases of death was overall good. Of the 42 respondents who have been studied, 90.5% have a good level of knowledge, and 9.5% have a enough level of knowledge. Being a general practitioners at RSD Gunung Jati Kota Cirebon have good and enough knowledge about the determination natural death and unexpected unnatural cases of death